SISTEM MONITORING LAYAR KOMPUTER SECARA REMOTE MENGGUNAKAN JARINGAN MULTIDROP RS 485 - Kristanto, Irwan; Thali, Tony Chandra; Sahli, Irwan (Institute of Research and Community Outreach - Petra Christian University, 1999)
Serial communication is commonly used in PC interface, but serial communication that is commonly used is RS-232 which only could communicate in one to one scheme. This paper will explain a software using the RS-485 interface that can communicate in one to many scheme using a multidrop network system. The server will monitor slave computer, so from the master computer we will be able to see what kind of application is being done in the slave computer. Software has been designed under Windows environtment (32 bit) using Delphi 3.0 from Borland International, Inc Software. There are two kinds of software : master and slave. The master software will control the computer we want to monitor, while the slave software will send the monitor picture to the master. The system hardware uses 3 RS 232 to RS 485 converter installed at the 3 PCs, one converter is used by master, and 2 converters are used by slave computers. Testing of picture compression, picture transmission with varying transmission speed have been done in this experiment. Abstract in Bahasa Indonesia : Komunikasi serial banyak sekali digunakan dalam interface PC namun serial yang biasa dipakai adalah RS-232 yang hanya dapat berhubungan secara one to one. Dalam paper ini dibuat software menggunakan sistem RS-485 yang dapat berhubungan secara one to many menggunakan sistem multidrop network. Aplikasinya adalah monitoring komputer, jadi dalam sebuah komputer dapat melihat apa yang sedang dikerjakan oleh komputer lain dengan melihat layar monitor komputer tersebut. Software dibuat berbasis Windows (32 bit) dengan bantuan Delphi 3.0 dari Borland International, Inc Software. Software terdiri dari dua yaitu master sebagai pengontrol untuk melihat komputer lain sedangkan slave sebagai pengirim gambar pada komputer yang dimonitor dan bersifat resident dan aktif. Hardware yang digunakan adalah 3 buah RS 232 to RS 485 Converter yang dipasang pada 3 buah PC dimana sebuah PC digunakan untuk master dan 2 buah PC untuk slave. Pengujian secara software dilakukan pada pengecekan kebenaran pengiriman data, pemadatan gambar, pengiriman gambar pada berbagai kecepatan transmisi. Kata kunci: sistem monitoring jarak jauh, monitor komputer, jaringan multidrop RS485